The Effect of Paired Lower Passing Exercises on the Improvement of Lower Passing in Volleyball Games at Iqra High School, Bengkulu City - Habibaen, Hifdi Mualim Al (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
This study aims to determine the effect of underhand passing exercises on the ability of underhand passing techniques at IQRA High School volleyball club Bengkulu City. This research method is an experimental research that uses a one group pretest posttest design. The population of this study were the 14 children of the IQRA SMA Club volleyball athletes in Bengkulu City. The test instrument used to measure lower passing ability is a modified braddy volley ball test. Data analysis techniques using hypothesis testing with t-test analysis. The results showed that there was an effect of underhand passing training on the ability of underhand passing technique at IQRA High School volleyball club Bengkulu City, with a t count of 6.996 and t table of 2.160 with a p significance value of 0.000. Because t count is 6.996> t table is 2.160, the significance value is 0.000 <0.05 and the percentage increase is 6.21%.)